2015
DOI: 10.1068/p7779
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Driving in Low-Visibility Conditions: Does Stereopsis Improve Speed Perception?

Abstract: Laboratory-based studies of perceived speed show that, under most circumstances, perceived speed is reduced as a function of contrast. However, a recent investigation of perceived vehicular speed while driving around a closed road circuit showed no such effect (Owens, Wood, & Carberry, 2010, Perception, 39: , 1199-1215). We sought to probe the source of this discrepancy, asking whether the presence or absence of stereoscopic motion information might account for the difference in results. In a two-alternative f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 59 publications
4
21
1
Order By: Relevance
“…Our JND estimates are generally consistent with figures obtained under quite different laboratory conditions, stimuli and paradigms in humans 10 , 11 and in monkeys 12 , as well as with more or less realistic optic flow stimuli in car driving contexts 13 16 . However, we also directly compared the results obtained in a classical laboratory setting (second experiment) with those obtained in a condition that mimicked home TV watching (first experiment), showing in the latter case an even poorer sensitivity to altered video speed.…”
Section: Discussionsupporting
confidence: 87%
“…Our JND estimates are generally consistent with figures obtained under quite different laboratory conditions, stimuli and paradigms in humans 10 , 11 and in monkeys 12 , as well as with more or less realistic optic flow stimuli in car driving contexts 13 16 . However, we also directly compared the results obtained in a classical laboratory setting (second experiment) with those obtained in a condition that mimicked home TV watching (first experiment), showing in the latter case an even poorer sensitivity to altered video speed.…”
Section: Discussionsupporting
confidence: 87%
“…Driving simulation studies showed that participants in computer-generated driving simulations not only perceived foggy (vs. clear) scenes to move more slowly [ 19 ] but also “drove” faster than a given target speed in simulated fog [ 20 ]. This finding was replicated using filmed footage of actual traffic situations [ 21 , 22 ]. However, these studies have been criticized for representing a poor model of motion perception in three-dimensional environments, because contrast was reduced uniformly and independently of distance.…”
Section: Introductionmentioning
confidence: 73%
“…His findings suggest that the sense of vection is strengthened by stereoscopic informationnot by way of disambiguating optic flow and environmental depth, but rather by feeding an additional channel for motion in depth, which independently supports the sense of vection. Similarly, perceived egomotion speed from video clips of car driving is higher if the clips are stereoscopically presented (Brooks & Rafat, 2015). Gray and Regan (1998) investigated the role of stereoscopic disparities and image expansion in the perception of time to collision and found that accuracy and discrimination are best if both cues are available.…”
Section: Introductionmentioning
confidence: 99%